Penguatan Sinergitas Kelembagaan dan Supervisi Manajerial Kepala Sekolah bersama Perwakilan YPLP PGRI Kabupaten Lampung Timur - Putri Sandora; Hajar Wahyuni; Moch. Amrodji; Didik Eko Putro; Syahrul Munir (Pusat Riset dan Inovasi Nasional, 2026)
The success of managing private schools under the auspices of PGRI is highly dependent on harmonious synergy between the Yayasan Pembina Lembaga Pendidikan (YPLP) and the school units. This community service program aims to strengthen the managerial capacity of school principals and improve institutional administrative order through supervisory assistance in collaboration with YPLP PGRI of East Lampung Regency. The partners in this activity were schools within the YPLP PGRI East Lampung network that were identified as requiring intensive guidance.The implementation method employed a Participatory Action Research (PAR) approach, consisting of the following stages: (1) mapping the current condition of school quality; (2) conducting Focus Group Discussions (FGDs) related to institutional regulations; (3) assisting in the preparation of managerial documents; and (4) conducting clinical supervision. The activities involved YPLP administrators, school principals, and teaching staff.The results of the program indicate: (1) an increased understanding among school principals of their main duties and functions as well as their working relationships with the foundation; (2) the development of well-organized and standardized school governance documents; and (3) the implementation of constructive managerial supervision, as evidenced by the submission of supervision outcome documents. The synergy among academics, foundations, and schools has proven effective in fostering a healthy and accountable organizational climate..